Assessment of Training Level and Access to ICT Facilities on ICT Competency of Business Education Lecturers in Colleges of Education in North East Nigeria - Sheriff, A. O; Inuwa, U. (Kashere Journal of Education, 2021)
The study assesses the training level and access to ICT facilities on ICT competency of business education lecturers in colleges of education in North East Nigeria. A quantitative survey method was employed, using a cross-sectional research design. The population of the study comprised 146 business education lecturers and the entire population was used in the study. The data was collected through self-administered questionnaires from 146 respondents. The study indicated that ICT is a transformational tool that has promoted the shift to a learner centered environment. It has assisted in improving the quality of education and training by increasing learners’ motivation and engagement, facilitating the acquisition of basic skills. The study employed the multiple regression method; the findings indicated that level of ICT training and access to ICT facilities has a significant positive relationship with the ICT competency of business education lecturers in colleges. The conclusion provided some limitations and offer suggestions for future research directions.